Electronic books for experts and users - Zdeněk Hlávka (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
The paper describes our experience with the production of electronic textbooks. Electronic books are defined as supplements to usual printed textbooks. The first part of the paper describes the technical background of our electronic book system. In the second part we describe how this system can be used also by authors who do not want to spend too much time with setting up the system and learning all of the (un)necessary technical details. The last section discusses various forms of distribution of electronic books.
urn:nbn:de:kobv:11-10050213
Keywords: 330; Elektronisches Publizieren; Internet; E-book